Single-Phase Voltage-Doubler High-Power-Factor Ćuk Rectifier Operating in Discontinuous Conduction Mode - Mateus Nava Mezaroba; Carlos Henrique Illa Font; Telles Brunelli Lazzarin (IEEE Open Journal of the Industrial Electronics Society, 2024)
This article provides a comprehensive analysis, including static, dynamic, and experimental validation, of a voltage-doubler Ćuk rectifier operating in the discontinuous conduction mode (DCM) for single-phase applications. The proposed topology integrates two classic Ćuk rectifiers through a three-position switch, allowing for either a doubled output voltage or reduced voltage efforts compared to the conventional topology. The voltage gain is increased while maintaining the step-up/step-down characteristic of the Ćuk family, and power components are activated only in a half cycle of the electrical grid, thus reducing the current efforts in the semiconductors. These features make the Ćuk converter suitable for higher voltage applications. The proposed topology is analyzed in DCM, where a high power factor is naturally achieved without a current control loop. An experimental prototype of 1 kW is built to verify the theoretical analysis, and the results show an efficiency of 94.68% with an input current total harmonic distortion of 1.86% at a rated power, including an output voltage control loop. Furthermore, the proposed topology is compared to the conventional Ćuk rectifier, both operating in DCM and with power factor correction.